How do Performance Targets Affect Future Performance by Students and Schools? - Marcello Sartarelli; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
The paper examines whether meeting performance targets in tests at school has an effect on students' subsequent achievement in education and the take-up by schools of financial support from the government for students. We build a theoretical model to describe the channels through which students' belief of their ability, as proxied by previous performance in tests, affect their current effort in preparing for a test, and how previous performance affects the effort in teaching by a school. We find that an increase in the performance target in the first test has an ambiguous effect on the effort exerted for the second test. A higher performance target in the current test increases the effort of low-ability students and teaching effort for low ability students, while it has an ambiguous effect on high ability ones. Finally, an increase in government funding per student increases the effort by students.
Keywords: I22; I28; 330